2014
DOI: 10.1523/jneurosci.5232-13.2014
|View full text |Cite
|
Sign up to set email alerts
|

Dissociable Neural Networks Supporting Metacognition for Memory and Perception

Abstract: Review of Baird et al.Metacognition in its broadest sense refers both to knowledge about our mental abilities and to the regulatory processes by which we might use that knowledge to control cognition; for example, changing how we perform a task if we feel our current strategy is not optimal (FernandezDuque et al., 2000). While there is debate over the extent to which metacognition relates to existing models of monitoring and cognitive control, the term is generally applied to instances where self-knowledge is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 11 publications
(10 reference statements)
1
8
0
Order By: Relevance
“…“Thus understanding any metacognitive judgment must involve understanding the cognition it measures and the multiple processes that contribute to the judgment” ( Schwartz and Diaz, 2014 , p. 9). Attempts at componential analysis of metacognition are in their infancy ( Fleming and Lau, 2014 ; Garrison, 2014 ), but they appear to be fruitful with regard to understanding its impact upon visual perceptual tasks. Nevertheless, the investigation of the neural basis of metacognition ( Baird et al, 2013 ) is not without its limitations.…”
Section: Expertise and Metacognitionmentioning
confidence: 99%
“…“Thus understanding any metacognitive judgment must involve understanding the cognition it measures and the multiple processes that contribute to the judgment” ( Schwartz and Diaz, 2014 , p. 9). Attempts at componential analysis of metacognition are in their infancy ( Fleming and Lau, 2014 ; Garrison, 2014 ), but they appear to be fruitful with regard to understanding its impact upon visual perceptual tasks. Nevertheless, the investigation of the neural basis of metacognition ( Baird et al, 2013 ) is not without its limitations.…”
Section: Expertise and Metacognitionmentioning
confidence: 99%
“…This work is well underway. An increasing number of empirical studies and reviews that reveal how the brain facilitates effective task performance have been published (Badre and D'Esposito, 2007 ; Burgess et al, 2007 ; Koechlin and Hyafil, 2007 ; Forbes and Grafman, 2010 ; Badre et al, 2011 ; Fleming and Dolan, 2012 ; Garrison, 2014 ; Clark and Dumas, 2015 ). At the turn of the century, in the US, the National Academy of Sciences ( 2000 ) advised that “neuroscience has advanced to the point where it is time to think critically about the form in which research information is made available to educators so that it is interpreted appropriately for practice—identifying which research findings are ready for implementation and which are not.” By Goswami ( 2004 ), in the UK, Goswami had stated that neuroscience had led to the discovery of “neural markers” that can be used to assess development.…”
Section: Toward a Trans-disciplinary Perspective On Educational Reseamentioning
confidence: 99%
“…The prefrontal cortex (PFC; See Figure 1 ) has been isolated as the core brain region for meta-cognition (Middlebrooks and Sommer, 2012 ; for review see Fleming and Dolan, 2012 ). The proposition that meta-cognition is under neural control is supported by a burgeoning amount of neuropsychological literature (e.g., Fleming and Dolan, 2012 ; Garrison, 2014 ). Neuroscientific studies have suggested that a defining function of the anterior PFC may be meta-cognitive awareness, or the process of reflection upon one's own mental contents (Nelson and Narens, 1990 ; Stuss, 2011 ; Fleming and Dolan, 2012 ; Garrison, 2014 ).…”
Section: Neural Structures Recruited During Meta-cognitionmentioning
confidence: 99%
See 2 more Smart Citations